Study of Solute Solvent Interaction Through Dielectric Properties of Allyl Chloride with Ethanol - G.M. Dharne; Aruna. P. Maharolkar; S. S. Patil; P.W. Khirade (International Journal of Pharma and Bio Sciences, 2010)
Dielectric relaxation measurements of Allyl Chloride (AC) with Ethanol mixture for different concentrations over the frequency range 10MHZ to 20GHZ at 308K and 318K have been carried out using Picoseconds Time Domain Reflectometry (TDR). Static permittivity (ε0), dielectric constant at high frequency (ε∞) and relaxation time (τ) were found through dielectric measurements. The Bruggeman factor (fB), Kirkwood correlation factor (geff), excess static permittivity (ε0E), and excess Inverse relaxation time (1/τ) E were determined and discussed to yield information on the intermolecular interactions and the Dynamics of the mixture of the system.